2014
DOI: 10.1038/bmt.2014.254
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism analysis in peripheral blood using indel quantitative real-time PCR is a useful tool to predict post-transplant relapse in acute leukemia

Abstract: Detection of increasing mixed chimerism (IMC) using standard PCR correlates with relapse after allo-SCT for acute leukemias (ALs). Quantitative real-time PCR of insertion/deletion polymorphism (indel qrtPCR) is a much more sensitive method, which can be performed on peripheral blood. We studied the significance of low increases of recipient cells (0.1%) detected by indel qrtPCR in a cohort of 89 transplants. We did not observe relapse among the 32 patients with no IMC. Fifty-seven patients presented a first IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 41 publications
6
40
0
1
Order By: Relevance
“…Recipient DNA in low levels could be caused by surviving leukemic blasts, host hematopoietic cells, cells of non‐hematopoietic origin, or a combination of these. Most studies of RQ‐PCR chimerism have used absolute detection levels of 0.1%‐1% recipient DNA as clinically relevant cutoffs, although results from definitions based on increasing donor DNA rather than absolute levels have been reported in adults . In our study, we detected stable recipient DNA at least once during follow‐up in all children and 56% (347/610) of samples had values above detection limit.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Recipient DNA in low levels could be caused by surviving leukemic blasts, host hematopoietic cells, cells of non‐hematopoietic origin, or a combination of these. Most studies of RQ‐PCR chimerism have used absolute detection levels of 0.1%‐1% recipient DNA as clinically relevant cutoffs, although results from definitions based on increasing donor DNA rather than absolute levels have been reported in adults . In our study, we detected stable recipient DNA at least once during follow‐up in all children and 56% (347/610) of samples had values above detection limit.…”
Section: Discussionsupporting
confidence: 88%
“…This is supported by a recent study showing an increased proportion of T regulatory cells in patients with mixed compared to full donor chimerism . Thus, highly sensitive, sequential measurements of chimerism could provide information on the potency of the graft‐versus‐leukemia effect, with the potential of guiding interventions aimed at strengthening this effect …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…1, 2 Sensitive chimerism quantification may therefore allow for early therapeutic intervention, potentially improving treatment response. 3, 4 Frequently, post-HSCT chimerism monitoring involves bone marrow (BM) biopsies, although hematologic malignancies are frequently associated with risk factors for adverse events (for example, low platelet count) and dry taps can preclude chimerism analyses. 5, 6 However, new PCR strategies for chimerism quantification have dramatically increased technical sensitivity with current methods enabling the detection of chimerism below 0.1%.…”
mentioning
confidence: 99%
“…This fact has important consequences in the clinical application of real-time for chimerism, where usually only 3 replicates are performed. Jacque et al (2015), using a genomic real time approach with 250 ng of input DNA (Alizadeh et al 2002) had demonstrated that an increase of chimerism of 0.1% could be useful to exclude all the cases of the relapse. However, considering the higher cost and time consuming of the proposed protocol, compared to the standard one, we suggest to use the sNAS-qPCR method only when low DNA input amount is available, as in the case of blood cell subset samples.…”
Section: Discussionmentioning
confidence: 99%